PHILOSOPHICAL BASIS OF FORMING ECOCULTURE IN ELEMENTARY STUDENTS PEDAGOGICAL BASIS OF IMPROVEMENT - Uljamol Shermatova (Scholar Express Journal, 2025)
This article is focused on the topic "Pedagogical foundations of improving the philosophical foundations of the formation of eco-culture in primary school students", and it is important to highlight the development of eco-culture in students from a scientific and pedagogical perspective. The article provides an analysis and suggestions on the philosophical and pedagogical foundations of the concept of eco-culture, as well as effective ways of forming eco-culture in the minds of primary school students.
Keywords: Primary; students; ecoculture